PENGEMBANGAN KEWIRAUSAHAAN DAN LITERASI KEUANGAN RUMAH LITERASI ASMA NADIA - Rafinda, Ascaryan; Suroso, Agus; Faturokhman, Agus; Gumintang, Bagas; Nikmah, Filda Khoirun (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Early entrepreneurship education is one of the strategic steps to shape children's character and skills in facing the development of the times. This paper reviews the entrepreneurship education program at the Asma Nadia Reading House, Tambaksogra Village, Sumbang District, Banyumas Regency, which aims to foster entrepreneurial interest and skills in children. The activities include making crafts from used bottles, making snacks, financial management training, introducing e-commerce, and product photography and graphic design training. The results of these activities show a positive impact on creativity, a basic understanding of entrepreneurship, digital literacy, and children's awareness of the importance of financial planning. This entrepreneurship education program has fostered children's interest in entrepreneurship and is expected to be a reference for children to start entrepreneurship.